THE RELATIONSHIP BETWEEN USING ARTIFICIAL INTELLIGENCE METHODS IN DEVELOPING DIGITAL MARKETING AT THE OIL MARKETING COMPANY - Researcher: Israa Abdel Hussein Issa; Dr. Hussein Muhammad Saad (American Journals, 2024)
The study aimed to demonstrate the relationship of the use of artificial intelligence in developing digital marketing at the Oil Marketing Company, by applying this study to the employees of the (SOMO) Oil Marketing Company, and on an innovation consisting of 120 people at the (SOMO) Oil Marketing Company in an intentional manner. The use was used Description Analytical, a statement regarding the variables of the study must be excluded, and it will be distributed to the colored figures of the study, and it will be compiled, analyzed, and the hypotheses for the study will be tested through the use of the statistical packages program (SPSS), where it has been communicated that: There is a statistically significant relationship between artificial intelligence in the development of digital marketing. There is a statistically significant relationship between the diversity in the use of social media in marketing in the development of digital marketing, and the existence of a statistically significant relationship between the diversity in digital advertising in the development of digital marketing, in addition to the existence of a statistically significant relationship between the diversity of after-sales services in The development of digital marketing, and the existence of a statistically significant relationship between the use of e-mail in the development of digital marketing.
Keywords: Artificial intelligence - marketing - digital oil marketing company.